Актуальні тенденції використання графічного контенту для брендингу в мережі Інтернет - Міненко, Катерина; Химиця, Наталя (Видавництво Львівської політехніки, 2019)
The theses deals with the pictures with text in the social media marketing. Special attention is given to the qualitative characteristics these pictures. The text gives a valuable information on a brand, a graphic content and a social media marketing.
Keywords: графічний контент; SMM; брендинг в Інтернеті; соціальні мережі